PENGARUH DIMENSI-DIMENSI EKUITAS MEREK TERHADAP NIAT BELI DENGAN KESEDIAAN KONSUMEN MEMBAYAR HARGA PREMIUM SEBAGAI VARIABEL INTERVENING (Studi Mahasiswa Pengguna Iphone di Indonesia) - Muhammad Reza Farid Nur Majid; Amie Kusumawardhani (Diponegoro Journal of Management, 2022)
Various business strategies have been carried out by the company to get a lot of profit. One of them is by setting a high price for the products offered. However, premium pricing can be a boomerang for companies. This strategy can only be applied if the brand equity of the company is high enough. Therefore, this study was conducted to examine the effect of brand awareness, perceived quality, brand association and brand loyalty on purchase intention with customer’s willingness to pay a premium price as an intervening variable. The population used in this study are students in Indonesia who have bought an Iphone smartphone. This study used a sample of 112 respondents who were selected using purposive sampling method. The data collected from the results of the questionnaire distribution was then processed and analyzed using the SPSS 25 and AMOS 26 programs. The results obtained in this study conclude that brand awareness, perceived quality, brand association and brand loyalty of Iphone smartphones have a positive effect on customer’s willingness to pay a premium price. Then customer’s willingness to pay a premium price also has a positive influence on purchase intention.